The Synergistic Effects of Li2SiO3-Coating and Si4+-Doping for LiNi0.5Mn0.5O2 Cathode Materials on the Structure and the Electrochemical Properties. Issue 12 (21st September 2017) - Yang, Guowei; Jia, Guofeng; Shangguan, Xuehui; Zhu, Zenghu; Peng, Zhengjun; Zhuge, Qin; Li, Faqiang; Cui, Xiaoling
Abstract : zLi2 SiO3 @LiNi0.5 Mn0.5 O2 (z = 0, 0.03, 0.05, 0.08) ("@" means "was coated on the surface of") cathode materials had been successfully prepared via a syn-lithiation strategy. The structure and the electrochemical properties were analyzed systematically. The results of the structural analysis showed that Li2 SiO3 was well coated on the surface of the material, and partial of Si 4+ was doped into the structure. In addition, the results of the electrochemical measurements suggest that 3 mol% Li2 SiO3 -coated LiNi0.5 Mn0.5 O2 electrode has the best electrochemical performance, including the highest capacity, best cycle stability and rate performance. The capacity retention is improved about 24% by 3 mol% Li2 SiO3 coating at 60°C. Additionally, all the resistances of the 3 mol% Li2 SiO3 @LiNi0.5 Mn0.5 O2 cathode material are considerably smaller than that of the un-doped material, which means it has a faster lithium-ion migration rate. This finding is in good agreement with the calculated results. In summary, Li2 SiO3 coating and Si 4+ doping can lower Li/Ni mixing, increase the structural stability, reduce polarization, decrease the migration resistance and improve the migration rate of the lithium-ion which, in turn, improves the electrochemical properties of LiNi0.5 Mn0.5 O2 .